EXPERIMENTAL STUDY ON THE OPTIMIZATION OF EXTRACTION PROCESS OF GARLIC OIL AND ITS ANTIBACTERIAL EFFECTS - Guo, Yajie (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Garlic oil which is the main active constituent of garlic has a wide range of pharmacological activities, and a broad antibacterial spectrum. It also has a strong anti-cancer activity, and can significantly inhibit a variety of tumors such as liver cancer, gastric cancer and colon cancer. The objective is to study the extraction process of garlic oil and its antibacterial effects.Materials and Methods: CO2 Supercritical extraction was used to investigate the optimal processing conditions for garlic oil extraction; filter paper test and suspension dilution test were applied to determine the bacteriostatic action of garlic oil. Results: In the CO2 supercritical extraction experiment, factors influencing the yield of garlic oil were: extraction pressure > extraction temperature > extraction time in descending order. Range analysis showed that the optimal experimental conditions for CO2 supercritical extraction of garlic oil were extraction pressure of 15 Mpa, temperature of 40 ℃, and duration of 1 h. Different concentrations of garlic oil could all inhibit the growth of Staphylococcus aureus, Escherichia coli and Bacillus subtilis, suggesting that garlic oil has an antibacterial effect. Conclusion: The optimal experimental conditions for CO2 supercritical extraction of garlic oil were: extraction pressure of 15 Mpa, temperature of 40 ℃, and duration of 1 h; garlic oil has an antibacterial effect.